A comparison of time series forecasting between artificial neural networks and box and jenkins methods - Collantes Duarte, Joanna; Colmenares La Cruz, Gerardo; Orlandoni Merli, Giampaolo; Rivas Echeverría, Franklin (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper deals with a comparison between Box and Jenkins methodologies and Artificial Neural Networks on time series forecasting. ARIMA and Transfer Function Models are compared with Neural Network Models. Performance oft he building models are analysed using comparative criteria during the prediction and fitness stage.